PERANAN PPAT DALAM PENDAFTARAAN TANAH ULAYAT MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Dwikornida, Yevendri dan (Normative Jurnal Ilmiah Hukum, 2025)
Land has a very important meaning and role for human life, because everyone needs land during their life until they die and considering the structure of life and the economic pattern of the majority of which is still agrarian and as a country with an agrarian system, land is a very suitable and complex livelihood for each person to achieve prosperity in various fields, where the land itself is also the basic capital in the development of a nation and its benefits must be managed as well as possible including customary land, namely rights that are inherent as a special competence in customary law communities, in the form of authority/power to manage and regulate land and its contents with internal and external validity. In connection with the ownership of rights to customary land, UUPA regulates land registration which aims to provide legal certainty as regulated in Article 19 which reads, "To guarantee legal certainty, the Government shall carry out land registration throughout the territory of the Republic of Indonesia according to the provisions regulated by Government Regulations". The Government Regulation in question is Government Regulation No. 24 of 1997 concerning Land Registration. In Article 37 number (1) of Government Regulation No. Law No. 24 of 1997 concerning Land Registration states: "The transfer of land rights and ownership rights to apartment units through sale, exchange, gift, investment in a company, and other legal acts of transfer of rights, except for transfer of rights through auction, may only be registered if granted by a deed drawn up by an authorized Land Deed Official (PPAT) in accordance with applicable laws." According to Article 1, number 24 of Government Regulation No. 24 of 1997 concerning Land Registration, a Land Deed Official (PPAT), hereinafter referred to as PPAT, is a public official authorized to draw up certain land deeds. Given the importance of PPAT, it is fundamentally closely related to legal acts concerning land rights. To prove legal acts concerning land rights, an authentic deed is required. A public official is someone who carries out some of the public functions of the state, particularly in the field of civil law. The public official referred to above is the PPAT.